Answer :

A =


A3 = A2.A


A2 =


=


A2.A =


=


=


Now, A3 – A2 – 3A – I



=


=


=


Thus, A3 – A2 – 3A – I


Now, (AAA) A – 1. – (A.A) A – 1 – 3.A A – 1 – I.A – 1 = 0


AA(A – 1A) – A(A – 1A) – 3(A – 1A) = – 1(A – 1I)


A2 – A – 3A – I = 0


= A – 1 =


Now,



=


=


=


Hence, A – 1 =


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If <span lang="ENMathematics - Board Papers

Using matrices soMathematics - Board Papers

<span lang="EN-USMathematics - Board Papers

Using properties Mathematics - Board Papers

Using matrices, sMathematics - Board Papers

If A is square maMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

The management coMathematics - Board Papers

If A is an invertMathematics - Board Papers

If <iMathematics - Board Papers